Adaptive algorithm of implantable insulin pump operation - Mustetsov, N. P.; Lapta, S. S. (Biophysical Bulletin, 2018)
Relevance: Diabetes mellitus is one of the leading causes of death. Low survival rates are caused by many individual complications during the time course of a disease. Usually, the therapeutic algorithm of insulin administration is prescribed by a doctor on the basis of general model assumptions on the dynamics of glycemic regulation process. Existing models have limitations, due to the complexity of taking into account the individual characteristics of a patient and limited number of monitored indicators of human body. Therefore the development of more adequate models of glycaemia and algorithms for the introduction of insulin, which take into account the current state of a patient, is an actual task.Objective: The purpose of work is the development of a mathematical model and an adaptive algorithm for operation of implantable insulin administrating device on the basis of the offered model of dynamics of glucose concentration in human blood.Materials and methods: To substantiate suggested model of glycaemia we have used methods of structural and parametric identification of homeostatic systems based on differential and integral equations. This approach made it possible to achieve compliance of our proposed model with experimental data obtained for the patients with type 1 diabetes.Results: Numerical experiments have shown the effectiveness of supposed model of glucose level dynamics in human blood for the development of an algorithm for normalizing glycaemia with the help of implantable insulin dispenser. The advantage of proposed algorithm is the ability to maintain the glucose level in patient's blood regardless of diet.Conclusions: Adoption of the developed dynamic model of glucose level in human blood provides a starting point for creation of operating algorithm for implanted insulin dosage device. For the known dynamics of glucose in patient’s body, exploitation of our individual adaptive algorithm of insulin administration allows to normalize the level of glucose in patient’s blood irrespective of diet, in contrast to the existing insulin pumps, which work according to the set program and require patient to adhere to the prescribed diet.